Lateral pelvic lymph node dissection can be omitted in lower rectal cancer in which the longest lateral pelvic and perirectal lymph node is less than 5 mm on MRI. Issue 3 (25th October 2013) - Ogawa, Shimpei; Itabashi, Michio; Hirosawa, Tomoichiro; Hashimoto, Takuzo; Bamba, Yoshiko; Kameoka, Shingo
Abstract Background and Objectives The goal of the study was to examine the use of magnetic resonance imaging (MRI) for identification of patients with lower rectal cancer who may benefit from lateral pelvic lymph node dissection (LPLD). Methods Diagnoses and oncological outcomes were examined in 160 cases. Patients in whom the long‐axis diameter of the longest detected lymph node was <5 mm or ≥5 mm were classified as LPLN(−) (n = 102) and LPLN(+) (n = 58), respectively. Results Diagnostic results gave a 21.6% positive predictive value (PPV) and a 95.0% negative predictive value (NPV) for the LPLN. These values were 59.6% and 91.5%, respectively, for the perirectal lymph node (PRLN). Multivariate analysis showed that a pathologic PRLN (pPRLN)(+) status was an independent prognostic factor for relapse‐free survival (RFS) (P = 0.0424) in the LPLN(−) group. The 5‐year RFS did not differ significantly between cases that did not and did undergo LPLD (90.0% vs. 83.8%) in the LPLN(−) and pPRLN(−) groups. Conclusions The low PPV and high NPV indicate that it is difficult to identify patients who may benefit from LPLD. However, the results show that LPLD has no benefit in LPLN(−) and PRLN(−) cases and that these cases can be identified based on MRI findings. J. Surg. Oncol. 2014 109:227–233. © 2013 Wiley Periodicals, Inc.